1999
DOI: 10.2307/2657230
|View full text |Cite
|
Sign up to set email alerts
|

Plant Removals in Perennial Grassland: Vegetation Dynamics, Decomposers, Soil Biodiversity, and Ecosystem Properties

Abstract: The consequences of permanent loss of species or species groups from plant communities are poorly understood, although there is increasing evidence that individual species effects are important in modifying ecosystem properties. We conducted a field experiment in a New Zealand perennial grassland ecosystem, creating artificial vegetation gaps and imposing manipulation treatments on the reestablishing vegetation. Treatments consisted of continual removal of different subsets or ''functional groups'' of the flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
250
7
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(283 citation statements)
references
References 87 publications
(115 reference statements)
22
250
7
4
Order By: Relevance
“…This strongly suggests that effects of species presence were by far more important than potential effects due to the increased number of interactions between species in the more diverse communities. Our observation is in accordance with Hooper and Vitousek's (1997) grassland diversity experiment and the study by Wardle et al (1999) from which the authors concluded that presence of specific plant functional types was a more important determinant of community productivity than was the number of functional types per se. The data from other studies of effects of grassland diversity on ecosystem function also are in line with this conclusion.…”
Section: Effects Of Species Diversitysupporting
confidence: 92%
“…This strongly suggests that effects of species presence were by far more important than potential effects due to the increased number of interactions between species in the more diverse communities. Our observation is in accordance with Hooper and Vitousek's (1997) grassland diversity experiment and the study by Wardle et al (1999) from which the authors concluded that presence of specific plant functional types was a more important determinant of community productivity than was the number of functional types per se. The data from other studies of effects of grassland diversity on ecosystem function also are in line with this conclusion.…”
Section: Effects Of Species Diversitysupporting
confidence: 92%
“…All ecosystems have a structure that is defined by the pools and fluxes of energy and matter in the system (Hannon 1973). The addition or removal of any one species or resource from a system can impact the strength of other interactions, especially when that species is a large component of net primary productivity (Wardle and Bonner 1999). Therefore, to better understand the impact of invasive species on an ecosystem, the interactions among EIMs are just as important as their individual changes in magnitude and direction.…”
Section: Discussionmentioning
confidence: 99%
“…Plant community biomass as well as plant community composition and diversity all have been identified as potential drivers of belowground community composition (Bardgett and Wardle 2010). The relative importance of these different factors for belowground community composition may depend on the functions of the soil biota considered (e.g., Wardle et al 1999, De Deyn et al 2011. Effects of plant community composition on soil biota may depend on their trophic position (Scherber et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some phyla of soil biota, such as nematodes, which include a wide variety of feeding types and trophic groups that can be studied in a quantitatively reliable way (Bongers 1990, Yeates et al 1993, Kardol et al 2010. It has been shown that plant functional groups can promote specific nematode feeding groups (Wardle et al 1999, Viketoft et al 2009, Sohlenius et al 2011, presumably because of differences in resource quality (Orwin et al 2010). However, also plant species within the same plant functional group can host quite different nematode communities (De Deyn et al 2004, Viketoft et al 2005, Sohlenius et al 2011 and plant diversities may affect nematodes in a species-specific way (Kostenko et al 2015).…”
Section: Introductionmentioning
confidence: 99%